Análise do conforto térmico em habitações de interesse social no Bairro Sumaré, Município de Sobral, Ceará - Braga, Marta Nélia Alves (2013)
One of the roles of housing is to protect individuals from the weather to which they are subject, saving inside a protection against the severities of the climate. When the house does n ot respect this principle of comfort, individuals are subject to the emergence of physical or psychosocial disorders. Studies show that thermal comfort directly influences productivity at work (Oliveira et al, 2010.), Yield of studies (Batiz; GOEDERT; MORS CH; Kasmirski - Jr; Venske, 2009) and especially in population health (Araujo, 2012). In this context, the main residents are affected as to mitigate the discomfort in their homes, they need to use artificial means of cooling, almost always, inconsistent wit h its income group. The proposed study aims to evaluate the thermal performance of single - storey and single - family dwellings built and in use Sumaré neighborhood in the city of Sobral / Ceará, and the thermal comfort of its users. To this end, we preserve housing characteristics of the original design were chosen. Selected dwellings are part of a city program to build housing in order to meet the population living in risk areas prone to flooding. The method used for performance evaluation based on requireme nts and criteria proposed by the NBR 15220 (ABNT, 2005), which are obtained from the mathematical calculation of thermal parameters that consider the performance of the building components. It was also evaluated the perceptions of users through questionnai res that were applied in July and August 2013 The degree of satisfaction was checked according to the Estimated Mean Vote (PMV - Predicted Mean Vote) suggested by Fanger and regulated by the International 7730 Organization for Standardization (ISO, 2005) a nd American Society of Heating, Refrigerating and Air - Conditioning Engi neers (ASHRAE, 2004). In parallel, measurements were made of the internal and external temperatures using thermo - hygrometer to compare with the opinion of the respondents. The results show that the tested housing have poor thermal performance. Regarding the results of the interviews, it can be noticed that the calculated thermal performance reflects the opinion of respondents who consider their thermally uncomfortable dwellings.